Niger : Poverty Reduction Strategy Paper; 2004 Status Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper discusses key findings of the 2004 Status Report on Poverty Reduction Strategy Paper (PRSP) for Niger. The report assesses economic and financial performance, as well as progress in implementing sectoral policies and strategies in 2004. Analysis of the economic and financial situation in 2004 confirms the vulnerability of Niger's economy to the vagaries of the weather, as reflected in a fluctuating rate of economic growth. The growth rate in 2004 was -0.6 percent, versus 3.8 percent in 2003, owing to a drop in agricultural output.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet